Winning people round to change in a week - Willcocks, Graham (Successful business in a week, 2000)
A manager's job is to get the best from individuals and teams, and knowing what makes people tick - collectively and individually - is the starting point for producing excellent results. This manual brings the topics of change and motivation together, demonstrating that they are not two different things but two sides of the same human situation. It takes the reader through the key points about what motivates people to work hard and produce results, and puts it in the context of change. The book should help the reader to: understand what makes people tick and what motivates them; maintain and improve morale when the going gets tough; get better results from individuals and teams who feel threatened by change; plan and handle the process of change productively; and keep it all going while change is happening - and beyond.